2012
DOI: 10.1100/2012/496579
|View full text |Cite
|
Sign up to set email alerts
|

Rediscovering Recovery: Reconceptualizing Underlying Assumptions of Citizenship and Interrelated Notions of Care and Support

Abstract: Over the last few decades, research, policy, and practice in the field of mental health care and a complementary variety of social work and social service delivery have internationally concentrated on recovery as a promising concept. In this paper, a conceptual distinction is made between an individual approach and a social approach to recovery, and underlying assumptions of citizenship and interrelated notions and features of care and support are identified. It is argued that the conditionality of the individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 51 publications
(104 reference statements)
3
38
0
Order By: Relevance
“…In the last decades, marked by the deinstitutionalization of residential services and the development of community-based services, "recovery" became popular in mental health care in Flanders (Vandekinderen et al, 2012). "Recovery" is defined as "enabling people with mental health problems to 'regain control over their lives, and .…”
Section: Ethical Aspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last decades, marked by the deinstitutionalization of residential services and the development of community-based services, "recovery" became popular in mental health care in Flanders (Vandekinderen et al, 2012). "Recovery" is defined as "enabling people with mental health problems to 'regain control over their lives, and .…”
Section: Ethical Aspectsmentioning
confidence: 99%
“…In recovery-oriented practice, an attempt is made to "reach beyond our storehouse of writings that describe psychiatric disorder as a catastrophic life event" (Ridgeway, 2001, p. 335), and priority is given to embracing strengths rather than weaknesses, hope rather than despair, and engagement and active participation in life rather than withdrawal and isolation (Secker, Membrey, Grove, & Seebohm, 2002;Leamy, Bird, Le Boutillier, Williams, & Slade, 2011). We argue, however, that it is necessary to theorize underlying notions of the human subject when studying how service users are approached in recovery-oriented mental health care (see Vandekinderen, Roets, Roose, & Van Hove, 2012). When people with mental health problems are expected to become self-responsible citizens, the responsibility for leading a fulfilling life is individualized (Craig, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The most common distinction of recovery in psychiatric care is that made between personal and clinical recovery (Macpherson et al 2015). Another distinction, between the personal and social approach to recovery has also been made (Vandekinderen et al 2012). This division is supported by a qualitative study where it was shown that the recovery process after hip replacement could lead to changes in personal and social functioning that patients did not always anticipate (Grant et al 2009).…”
Section: Quality Of Recoverymentioning
confidence: 99%
“…while they are cast as the dependent other, when they do attempt to gain a foothold on the ladder of individualism then they are expected to demonstrate extra-special, hyper- Hence, the focus of this notion of recovery relies on the characteristics and motivation of people with mental health problems rather than on discourses, policies and practices of the 30 support system (Vandekinderen, Roets, Roose & Van Hove, 2012). In our view, this individual approach to recovery leads easily to residual social practices, in which, chiefly, an economic rationality is brought to bear on social problems (Cruikshank, 1999).…”
mentioning
confidence: 99%